Multi-Drug Resistant Bacterial Strains in Lower Respiratory Tract Infections, Antibiotic Sensitivity Patterns and Risk Factors - Sherchan, Jatan B; Gurung, Pranita; Bam, Dirgh Singh; Sherchand, Jeevan Bahadur (Nepal Journal of Science and Technology, 2013)
Isolation of multidrug resistant bacteria such as extended spectrum beta-lactamase (ESBL), metallo beta–lactamase (MBL) producing and Methicillin resistant Staphylococcus aureus (MRSA) causing lower respiratory tract infection (LRTI) is associated with various risk factors and a major challenge in treatment. So, the study determined bacterial etiology of lower respiratory tract infection and antibiotic sensitivity pattern with special reference to ESBL, MBL, and MRSA strains along with risk factors associated with such strains. A total of 120 specimens were collected from patients with lower respiratory tract infection along with clinical details. Combination disk method was done for the detection of ESBL and MBL producing isolates and oxacillin disc was used to detect MRSA. Out of 120 specimens, 87.5% was monomicrobial while 12.5% was polymicrobial infection. Pseudomonas aeruginosa (36.19%) was the predominant followed by Acinetobacter baumannii (28.57%), Klebsiella pneumoniae (20.95%), Escherichia coli (8.57%) and Staphylococcus aureus (5.72%). Total 33 (31.43%) out of 105 monomicrobial isolate were MDR. All MDR E. coli, K. pneumoniae, P. aeruginosa were ESBL producers and (6, 20%) out of total A. baumannii isolated produced MBL and was not found to produce ESBL. All MDR S. aureus isolates were found to be resistant to methicillin. Carbapenems followed by amikacin were found to be the most effective antibiotic for Gram negative bacilli causing LRTI. Vancomycin, Teicoplanin & Linezolid were found to be the most effective antibiotics for MRSA. 28 out of 33 MDR isolate possessing patients had comorbid illness. Isolation of MRSA, ESBL and MBL producing bacteria in LRTI are increasing in number. Increased prevalence of MDR bacterial strains form patients with comorbid illness is a major problem in healthcare centers. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 157-163 DOI: http://dx.doi.org/10.3126/njst.v13i1.7454